2022
DOI: 10.1097/cr9.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Adolescent and Young Adult Cancer Services

Abstract: Background: The COVID-19 pandemic led to systemic change within healthcare settings. Policies were enacted in order to protect vulnerable cancer patients, meaning the landscape of service provision was significantly altered. Objective: To evaluate the experiences of young cancer patients and their caregivers during the first wave of the pandemic, to inform future service provision. Method: Semistructured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, evidence suggests young people with cancer have poorer mental health than their non-cancer peers [57] and poorer mental health was associated with increased healthcare utilization [25]. There is evidence of an increase in mental health concerns in this population following the COVID-19 pandemic [3,22,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, evidence suggests young people with cancer have poorer mental health than their non-cancer peers [57] and poorer mental health was associated with increased healthcare utilization [25]. There is evidence of an increase in mental health concerns in this population following the COVID-19 pandemic [3,22,34].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, there used to be a dichotomy in AYAs' receipt of healthcare-some being treated in pediatric services, and some in disease-centered adult oncology services. Given the specific biology of AYA cancers, specificity of late effects, as well as age-related developmental differences compared to children and adults, this model resulted in a large level of unmet need [2][3][4]. This led to a motivation to shape the care of AYAs in an ageappropriate manner-namely care services tailored and focused on the developmental particularities posed by the age of the patients, rather than being disease-specific [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core to these experiences were the healthcare professionals working to support these young people. Previous research has found that young people and their caregivers put great value on having staff who are kind and supportive, with an emphasis on staff who take the time to get to know patients and their families beyond the elements of routine care 27…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that young people and their caregivers put great value on having staff who are kind and supportive, with an emphasis on staff who take the time to get to know patients and their families beyond the elements of routine care. 27 A primary aim of TYA cancer care is offering services above and beyond cancer treatment, with a particular emphasis on the holistic needs of young patients. Healthcare workers play a pivotal role in this.…”
Section: Discussionmentioning
confidence: 99%